EXPLORING STUDENTS’ HABITS IN ENHANCING ENGLISH-SPEAKING ABILITY: A STUDY AT THE FACULTY OF PSYCHOLOGY, BUANA PERJUANGAN KARAWANG UNIVERSITY - Anggun Pertiwi; Nur Ainy Sadijah; Hilda Tri Yulianti; Depi Prihamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Considering the importance of English-speaking ability in both academic contexts and daily communication, this study explores students’ everyday habits that support the mastery of speaking, including fluency, pronunciation, and verbal interaction. The purpose of this research is to identify habits that contribute to the development of English-speaking ability among students. A qualitative descriptive approach was employed, with data collected through classroom observation and in-depth interviews. The participants were second-semester students from the Psychology Study Program, Faculty of Psychology, Universitas Buana Perjuangan Karawang. The findings reveal eight key habits that enhance speaking performance: practicing self-monologues, watching films and repeating vocabulary, listening to songs, recording new vocabulary, reading English texts, engaging in social interaction, using learning applications, and setting gadgets to English. These habits indicate that effective English learning extends beyond formal instruction and is shaped by reflective, contextual, and sustained personal practices. The study provides implications for the development of adaptive learning strategies that integrate cognitive and behavioral aspects of language acquisition.